An efficient one-pot protocol for the conversion of benzaldehydes into tetrazole analogs. Issue 5 (3rd February 2016) - Khan, Khalid Mohammed; Fatima, Itrat; Saad, Syed Muhammad; Taha, Muhammad; Voelter, Wolfgang
Graphical abstract: Abstract: An efficient protocol has been developed for the one-pot synthesis of tetrazole derivatives in moderate to good yields starting from substituted benzaldehydes and proceeding via non-isolated oxime and nitrile intermediates. The structures of the desired products were confirmed by IR, and NMR spectroscopy as well as mass spectrometry. A plausible reaction mechanism is also discussed.